Ovarian steroid cell tumor (not otherwise specified) with subsequent spontaneous pregnancy after tumor removal: a case report and literature review - Phawat Matemanosak; Krantarat Peeyananjarassri; Chitkasaem Suwanrath; Saranya Wattanakumtornkul; Satit Klangsin; Ekasak Thiangphak; Kanet Kanjanapradit (Taylor & Francis Group, 2023)
Steroid cell tumors not otherwise specified are rare sex cord-stromal tumors of the ovary that may produce various steroids and are associated with hirsutism and virilization. We report a rare case of ovarian steroid cell tumor with subsequent spontaneous pregnancy after tumor removal. A 31-year-old woman presented with secondary amenorrhea, hirsutism, and inability to conceive. Clinical and diagnostic evaluations revealed a left adnexal mass and elevated serum total testosterone and 17α-hydroxyprogesterone levels. She underwent a left salpingo-oophorectomy, and histopathological examination confirmed the diagnosis of a steroid cell tumor not otherwise specified. Her serum total testosterone and 17α-hydroxyprogesterone normalized one month after surgery. Her menses resumed spontaneously one month after the operation. She spontaneously conceived 12 months after the surgery. The patient had an uncomplicated pregnancy and delivered a healthy male infant. In addition, we reviewed the literature on steroid cell tumors not otherwise specified with subsequent spontaneous pregnancies after surgery and data regarding pregnancy outcomes.